PERKEMBANGAN JIWA NABI MUHAMMAD - Anwar Supenawinata (Psympathic : Jurnal Ilmiah Psikologi, 2008)
Man as creature that created by God (khaliq) as khalifah on the earth to carry out the commandment that able to rule, guide, care and maintain the worldwide to serve the God. The prefer man in order to be a good man certainly was destined by Allah Swt with the choise that has been decised by Him. Khaliq as the creature’s (man) creator that perfectly in his creature because consist of the body organs including soul and body, both are the reason why men get a task as khalifah on the earth which differs them from other creature on the earth. Mens in their life have their particular (goodness) and lack (mistake), these show that mans behavior rise down in accord of degree of their each knowledge and experience, thus a Prophet as ordinary people that in his course (development) can not escape from any mistakes.